Polymerised mite allergoids with glutaraldehyde reduce proteolytic activity and enhance the stability of allergen mixtures: a proof of concept with grass mixtures - Tudela, José Ignacio; Soria, Irene; Abel-Fernández, Eva; Cantillo, José Fernando; Fernández-Caldas, Enrique; Subiza, José Luis; Iborra, Salvador (Frontiers in Allergy, 2025)
BackgroundPolysensitized patients require allergen immunotherapy (AIT) targeting multiple allergens. However, combining allergen extracts can lead to instability and reduced efficacy particularly due to the high proteolytic activity of house dust mite (HDM) allergens. While is known that glutaraldehyde cross-linking may reduce enzymatic activity, its ability to stabilize multi-allergen formulations and protect key allergens from degradation remains unexplored.ObjectiveTo evaluate the impact of glutaraldehyde polymerization on the stability and immunogenicity of HDM and grass pollen allergen formulations, addressing proteolytic activity challenges in multi-allergen vaccines.MethodsStability was assessed over 24 months through protein quantification and antigenic activity assays. Proteolytic activity of HDM-containing extracts was measured using Azocoll, and peptide substrate-based enzymatic assays. Grass pollen allergen degradation was evaluated by SDS-PAGE, immunoblotting, and ELISA Immunogenicity was assessed in mice immunized with grass allergoids alone or in combination with glutaraldehyde-polymerised HDM, measuring IgG responses, splenocyte proliferation, and IL-10 production.ResultsGlutaraldehyde polymerization significantly reduced HDM proteolytic activity (p < 0.0001), achieving reductions of 97.7%, 77.9%, and 89.9% in total protease activity, cysteine protease activity, and serine protease activity, respectively. This inhibition protected grass pollen allergens when mixed with HDM from degradation, ensuring consistent protein content and antigenic activity over 24 months. Mice immunized with grass allergoids alone or combined with polymerised mite extracts showed similar IgG responses and T-cell activation, indicating no compromise in the immune response to grass allergens, with IL-10 secretion confirming preserved regulatory responses.ConclusionsPolymerised allergen extracts address the challenges of proteolytic degradation in multi-allergen formulations, offering stable, immunogenic vaccines that maintain efficacy and provide a reliable treatment option for polyallergic patients.